Women’s Empowerment in the Workplace from a Qur’anic Perspective: A Prophetic Gender Equilibrium Framework and Implications for Madrasah Education - Andi Nur Muwafiqah Takwa (LaKaspia, 2026)
Women’s participation in the workforce has expanded, yet unequal remuneration, career barriers, occupational segregation, and disproportionate care responsibilities continue to limit substantive gender equality. In madrasahs, which function both as educational settings and professional organizations, gendered expectations may also shape learning, employment, career development, and leadership. This study analyzes Qur’anic ethical foundations relevant to women’s agency and workplace participation, situates them in dialogue with contemporary evidence on structural gender inequality, and proposes a Prophetic Gender Equilibrium framework with implications for gender-responsive madrasah education and governance. The study employed qualitative-conceptual library research using thematic Qur’anic exegesis (tafsīr mawdū‘ī) and a gender-ecological perspective. The Qur’anic corpus comprised QS. An-Nisā’ 4:1, QS. At-Tawbah 9:71, QS. Āli ‘Imrān 3:35–37, QS. Al-Qaṣaṣ 28:23 and 28:26, and QS. An-Naml 27:23–44. Interpretations were examined through Indonesian thematic exegesis, Tafsir Al-Mishbah, and relevant scholarship, while contemporary workplace evidence was treated as secondary contextual material rather than as a direct Qur’anic finding. The analysis identifies shared human dignity (nafsin wāḥidah) and reciprocal social partnership (awliyā’) as ethical foundations directly traceable to the selected corpus. Three Qur’anic narratives provide complementary models of women’s agency: Maryam represents spiritual autonomy and personal development; the two women of Madyan illustrate professional responsibility, competence, and integrity; and the female ruler of Saba’ illustrates deliberative leadership. Khadijah is treated separately as a historical exemplar of economic agency. These elements are synthesized into the proposed Prophetic Gender Equilibrium framework across micro, meso, and macro levels. The proposed framework provides a structured conceptual bridge between Qur’anic ethics, contemporary workplace gender justice, and gender-responsive madrasah education. Its institutional and policy implications are normative-contextual applications rather than direct textual prescriptions. Because the framework remains conceptual, its dimensions and operational indicators require empirical validation before claims about effectiveness or generalizability can be made.